A new protocol (THIS and FAT) for the treatment of filler-induced vascular occlusion: a case series - Nazari, Shahriar; Fakih-Gomez, Nabil; Hadadian, Nima; Bayat, Foroohe; Bohlouli, Behnam; Muñoz-Gonzalez, Cristina; Pourani, Mohammad Reza (Frontiers in Medicine, 2025)
IntroductionHyaluronic acid (HA) fillers are generally safe; however, the most significant complication is vascular occlusion. Several therapeutic protocols have been proposed for managing ischemia. De Lorenzi introduced the HDPH protocol, which uses a minimum of 500 IU of hyaluronidase (HYAL) per ischemic area.Materials and methodsThis case series study evaluates the efficacy of a novel protocol, “THIS and FAT,” for managing ischemia resulting from filler-induced vascular occlusion (FIVO). The protocol builds on elements from previous approaches while introducing combination therapies specifically tailored to address ischemia. The therapeutic regimen includes T: botulinum toxin type A (BTX-A), H: high-dose HYAL, I: injectable platelet-rich fibrin (iPRF), S: serum platelet-rich fibrin (sPRF), a: aspirin and antibiotics, n: nanofat, d: debridement and dermabrasion, and F: fat membrane application.ResultsA total of 25 eligible patients, including 20 women and 5 men with a mean age of 32.36 ± 6.71 years, were included. The THIS and FAT protocol involved the injection of BTX-A and HYAL, with mean doses of 50.68 ± 60.79 Units and 5970.0 ± 2791.65 IU, respectively. Additionally, iPRF and sPRF were applied to the ischemic wound surface. Debridement was performed for ischemia classified as stage three or higher. Notably, 92% of patients treated with the THIS and FAT protocol showed complete improvement without scar formation.Conclusion“THIS and FAT” Protocol for managing ischemia following FIVO shows promising outcomes. Additionally, wound management with fat membrane, iPRF injections, sPRF dressing, and nanofat application resulted in favorable outcomes in this case series.